Radio propagation prediction for HF communications - Mudzingwa, Courage; Chawanda, Albert (Science Publishing Group, 2018)
The refraction and apparent reflection of HF radio waves by the ionosphere enables long range HF radio communications. The ionosphere is a distinctly irregular medium that is mostly driven by solar activity. Ionospheric models are useful in the prediction of ionospheric behaviour and in the provision of data required for the analysis and forecasting of ionospheric propagation. This paper provides a compact review of HF radio propagation prediction techniques and approaches for HF communications. The paper also highlights the numerous approaches have been used to date in an attempt to estimate F2 usable frequencies. The review presented in this paper is inspired by the most recent advances in the field of ionospheric prediction and modelling.